(3GfXeI GdYO aj GdMVGQGJ GdbOjeI h GdMGSHGJ GdGdcJQhfjI (B:s (3Ydhe GdceHjhJQ (B/s - (3eMehO, GHQGgje GdUZjQj s; (3GcQe GaOGQ s ((3OeTb (B:s (3eWGHY Gda HGA ddGOjH ,s)
(3GfXeI GdYO(B-(3GfXeI GdYO aj GdMGSHGJ GdGdcJQhfjI(B-(3GdYedjGJ GdMSGHjI(B-(3GdfXGe GdYTQj GdeQeR KfGFjG s
Keywords: (3GdMGSHGJ GdGdcJQhfjI s; (3MGShHs; (3GdceHjhJQs